(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Exposition writing learning is one of the materials in language learning that aims to expose information to readers. The purpose of this study is to determine which methods are effective in learning to write exposition through the concept of critical thinking. This study uses a quantitative research approach with methods of experimental design. A total of 68 students who were involved in this study were divided into two different treatment groups. Each group numbered 34 students. The first experimental group (A) applied the method Numbered Head Together, while the second experimental group applied the method Cooperative Script. In this study, the data were collected through a test of exposition writing skills in the two groups that had been given treatment in the learning process, namely the NHT group and CS. The results showed that learning activities by applying the cooperative learning Numbered Head Together was more effective than cooperative scripts. Students who learn with the NHT produced appropriate exposition writing and the structure exposition, such as, the selected topic, the presentation of the argument following the data and facts in the field, the disclosure of conclusions by emphasizing the core part of the topic being written, and using spelling and punctuation where there are only a few errors.